A genealogia do conceito de pessoa humana no Código Civil de 2002: uma história de sujeitos e relações de poder - Brunieri, Ariana Regina Storer (2019)
The presente work aims to go beyong what is normalized– from the letter of the law literalness - is essential to perform a device's ontology, to understand the historical context, the subjects, language and their discourses. The paper's investigative purpose is reply the following questions: What does the law say? Whom does the law tell? From these questions, sought to identify the discourse erected by the various voices of the state or society to conceptualize the human person in the homeland legal system. So, to analyze the outlook of the construction 2002 Civil Code became imperative to study the contributions of the devices, the games of force, the many voices and meanings to the private relations and people's lives daily regulation. That it was possible when observing the broader historical and social processes and at the same time make a microanalysis of the mixed states of tensions, trends and heterogeneous elements that make up the meaning given to the human person. Therefore, the methodological research was based on the French line discourse analysis and on the Michel Foucault devices, was used the genealogy to examine the human person founding values, searching for clues, excavating the linguistic marks left by enunciators (legislators) and all those who participated in the legislative process. The premise is to retell and to revisit the human person concept in the 2002 Civil Code, as a history of subjects and power relations.